Postcolonial Ecocriticism in Travel Memoir: The Paradox of Socio-Environmental Justice in Vladimir Arsenyev’s Novel Dersu Uzala - Pranantika Oktaviani (Balai Bahasa Provinsi Bali, 2022)
This research aims to reveal the colonial gaze and paradoxical sense of travel memoir on nature expedition conducted during Russian imperial era by explorer and scientist Vladimir Arsenyev. Arsenyev’s expedition to the Far East is memorized in his 1923 novel Dersu Uzala about Arsenyev’s indigenous guide Dersu. In this analysis, the theory used is postcolonial ecocriticism by Graham Huggan and Helen Tifffin on the correlation between the effect of colonialism in physical environment and its effect on relation between human and nature. Another theory used is from Reuel K. Wilson’s investigation of the motives behind various travel memoirs from the late nineteenth century. The main data of this qualitative research is gathered from relevant passages of the novel and analysed under postcolonial ecocriticism framework. The result shows the author’s paradox on disclosure of indigenous tribes as colonial ‘other’ in Russian Empire, the violation of hunting ethics by Russian explorers and the conflict between nature and urban development in Russia. AbstrakPenelitian ini bertujuan mengungkap pandangan kolonial dan paradoks dari memoar perjalanan expedisi alam yang dilakukan pada masa Kekaisaran Rusia oleh penjelajah dan ilmuwan Vladimir Arsenyev. Ekspedisi Arsenyev ke Timur Jauh diabadikan dalam novelnya yang menceritakan pemandu dari suku asli bernama Dersu. Dalam analisis ini, teori yang digunakan adalah kajian ekokritik pascakolonial yang dikemukakan oleh Graham Huggan dan Helen Tiffin mengenai hubungan antara efek kolonialisme pada lingkungan fisik dan efek pada hubungan antara manusia dengan alam. Teori lain yang digunakan berasal dari investigasi oleh Reuel K. Wilson mengenai motif dibalik memoar perjalanan pada akhir abad ke sembilan belas. Data utama pada penelitian kualitatif ini diperoleh dari bagian relevan pada novel dan kemudian dianalisis dengan konsep kajian ekokritik pascakolonial. Hasil analisis mengungkap adanya sikap paradox pengarang pada pandangan ‘liyan’ masyarakat kekaisaran Rusia terhadap penduduk asli, pelanggaran etika dalam berburu yang dilakukan penjelajah Rusia dan konflik antara alam dan pembangunan kota di Rusia.